Mid-term studio examination preparation by first year music degree students / Elmer Alfred, Fahmi Izzudin Aziz and Mohamad Sharul Azizi Jamian - Alfred, Elmer; Aziz, Fahmi Izzudin; Jamian, Mohamad Sharul Azizi (2019)
This study focused on " Midterms Studio Examination Preparation by First Year Music Degree Students ". This study is based on qualitative method which mean by interviewing the respondents and the data will be collected by analysis. The purpose of this study is to ascertain students' ability on how they prepare themselves to face mid-term studio exams and this study will be focusing on three main areas which are sight reading, scales for instruments and technical skills such as concone and vakkai for voice major, and pieces that they have been given by their own major instrument instructor. From this study, we found out that most of the respondents stated that lack of music background and experience is the main problem that they faced during the preparation. For first year degree music student, it is normal for them to not familiar with music notation but in this case it should not be used as an excuse to get low marks in every exam because, we all learnt from failure. Without failure, we will not going to learn anything. Midterm studio exams has their own requirement topic which are sight reading, scales for instruments and concone, vakkai for voice major students and repertoire. These three are the main topic or requirement to pass in midterm exam. Most of the respondents has the problem in sight reading since they are not familiar with those notation but we believe after a few more practice, they will slowly going to adapt with these kind of examination.